Estimation of Total Factor Productivity of Philippine Manufacturing Industries: The Estimates - Caesar B. Cororaton; Benjamin Endriga; Derrick Ornedo; Consolacion Chua (Philippine Institute for Development Studies (PIDS), 1995)
As suggested by vast literature, the Philippine economy has performed poorly over the last three decades due to deterioration in productivity. This paper provides an updated productivity estimates for the manufacturing industries over the period 1956-1992. This paper decomposes this industry productivity growth into technical progress and technical efficiency. It also analyzes the patterns of industry productivity through results of regression method.
Keywords: 330; total factor productivity; manufacturing sector; technical efficiency; output growth